Content Analysis of an ESP Textbook; English for Vocational High School - Asti Ramadhani E Lestari; Elyza Martiarini (Channing : Journal of English Language Education and Literature, 2021)
This research aimed at describing the result of English textbook analysis. The textbook is used as a medium for teaching English for Third-Grade students of Vocational Highschool in the second. This analysis verifies the appropriateness of the material that is contained in the book and used as a medium of teaching. The development of "Kurikulum Tingkat Satuan Pendidikan (KTSP)” in the national standards of education consists of content standard (Standar Isi), process, standard of grades competence (Standar Kompetensi Lulusan), teachers standard, facilities, management, funds, and the educational evaluation. The two of education national standards, Content Standard (Standar Isi) and Standard of Grades Competence (Standar Kompetensi Lulusan) are used as the main reference in developing the curriculum (KTSP). Those two standards are implemented to achieve the goals of the learning.